2013
DOI: 10.1074/jbc.m113.496802
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-Trisphosphate (IP3) Receptor Up-regulation in Hypertension Is Associated with Sensitization of Ca2+ Release and Vascular Smooth Muscle Contractility

Abstract: Background:The role of the vascular IP 3 receptor (IP 3 R) in hypertension is unknown. Results: IP 3 R are up-regulated in vascular smooth muscle (VSM) in hypertension through the calcineurin-NFAT pathway. Conclusion: Up-regulated IP 3 R in VSM sensitize Ca 2ϩ release and enhance contraction. Significance: Up-regulated vascular IP 3 R may contribute to vascular resistance in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Another study showed that absence of IP3 inhibited osteoblasts formation [39]. It was shown that IP3R can be up-regulated via Ltype calcium channels and this upregulation increased the stimulation of calcineurin and NFAT as well as osteoclast activation [40]. In our study, we suggest that amlodipine and lacidipine exert anti-osteoporotic effects by blockade of L-type calcium channels and both these are agents known to effect IP3R [41].…”
Section: Discussionmentioning
confidence: 55%
“…Another study showed that absence of IP3 inhibited osteoblasts formation [39]. It was shown that IP3R can be up-regulated via Ltype calcium channels and this upregulation increased the stimulation of calcineurin and NFAT as well as osteoclast activation [40]. In our study, we suggest that amlodipine and lacidipine exert anti-osteoporotic effects by blockade of L-type calcium channels and both these are agents known to effect IP3R [41].…”
Section: Discussionmentioning
confidence: 55%
“…For example, mesenteric VSM of ANG II-induced hypertensive mice and spontaneously hypertensive rats display elevated mRNA and protein levels of IP 3 R1 (Abou-Saleh et al, 2013). This increased expression was associated with sensitization of IP 3 R-mediated Ca 2+ release, resulting in augmented vasoconstriction in response to stimulation by vasoactive agents in ANG II-induced hypertensive mice.…”
Section: Sr Ca2+ Channelsmentioning
confidence: 99%
“…A recent study has shown that during hypertension InsP 3 R1 expression is activated in vascular smooth muscle cells in a NFATc-dependent manner (42). This increase in InsP 3 R1 sensitizes IP 3 -mediated Ca 2ϩ signaling.…”
Section: Discussionmentioning
confidence: 99%